Organization : contemporary principles and practices - Child, John, 1940- (Chichester, West Sussex : Wiley, 2015)
"The definitive organization management text for executives and aspiring business leadersOrganization: Contemporary Principles and Practices, Second Edition is the completely updated and revised landmark guide to "macro" organization theory and design, fully grounded in current international practice. International management expert John Child explores the conditions facilitating the development of new organizational forms and provides up-to-date coverage of the key developments driving new organization structure and practice. This revised Second Edition includes a new introductory section on Organization Theory as well as a complete Instructor Manual updated with new material on the basic principles of organizational design.With detailed case studies and examples from throughout the UK, Europe, Asia and North America, Organization provides a truly international overview for advanced students and business executives who want to be at the forefront of the evolution in Organization Theory. 21st Century organizations will be faced with entirely new challenges and opportunities than those faced by previous generations, and emerging business leaders must understand the new "macro" realities in order to succeed. Organization will help readers: Understand the "macro" organization, which is distinct from organizational behaviour Explore the way organizations fit into the international business environment and global economy Analyze the way organizational structure and design affect management performance Apply advanced organization theory and principles to day to day management activities Written by one of the foremost scholars, the fully updated Second Edition of this successful text provides executives and advanced business students with a wide-ranging and trustworthy guide to organizations as the conditions for their survival in our global business environment change"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Organizational behavior; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Organizational behavior; Electronic books; Electronic books